Analysis of Leadership and Organizational Culture on Employee Performance with Work Motivation as a Mediating Variable in the Revenue Agency of Batu Bara Regency - Susilawati Susilawati; Elfitra Desy Surya; Mesra B (Journal of Management, Economic, and Accounting, 2026)
Employee performance is a key factor in supporting the success of public sector organizations, especially local government agencies that play a direct role in serving the community. The Batu Bara Regency Revenue Agency is required to have employees with optimal performance to support the effectiveness of regional tax management and collection. This study aims to analyze the influence of leadership and organizational culture on employee performance with work motivation as a mediating variable at the Batu Bara Regency Revenue Agency. This study uses a quantitative approach with a survey method. The research population consists of all 100 civil servants (PNS) at the Batu Bara Regency Regional Revenue Agency, all of whom were included in the sample (population study). Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The results show that leadership and organizational culture have a positive and significant effect on employee performance and work motivation. Work motivation also has a positive and significant effect on employee performance. The mediation effect test shows that work motivation is not able to mediate the effect of leadership on employee performance, but it is able to mediate the effect of organizational culture on employee performance significantly. These findings indicate that a strong organizational culture can increase employee work motivation, which ultimately has an impact on improving performance. This study is expected to be taken into consideration by leaders in formulating human resource management policies that focus on strengthening organizational culture and increasing work motivation in order to encourage sustainable employee performance.